Sistem Keamanan Kendaraan Bermotor Dengan ESP32 Menggunakan Kontrol Android - Fahreza Aditya Aryatama; S. Samsugi (LPPM STIKI MALANG, 2024)
Motor vehicle theft throughout 2023 was 38,438 cases. One of the causes of motor vehicle theft is because the motor vehicle security system is still ineffective and there is no dual security system. This research aims to develop a motorcycle security system utilizing smartphones, specifically those based on the Android operating system, considering that almost everyone owns a smartphone. The increase in the number of motor vehicles is proportional to the rise in criminal activities, such as motorcycle theft. This system is designed to maximize the functionality of smartphones in daily life to enhance motorcycle security. The developed system connects Android to the ESP32 microcontroller using Bluetooth communication. Android acts as the user control medium, sending commands to the ESP32 via Bluetooth. The ESP32 then forwards these commands to the motorcycle, which responds according to the received instructions. The research results show that Android can be effectively used for motorcycle security, including activating the alarm, functioning as the motorcycle key, helping to locate the motorcycle in parking areas, receiving voice and button commands, and providing additional security features. Furthermore, this system allows users to utilize the SmartGuard Motor feature, which offers a primary motorcycle security system function connected via WiFi and Hotspot with a range of 50 meters. This study also demonstrates that Internet of Things (IoT)-based technology can be implemented to enhance the efficiency and security of personal transportation. System testing was conducted under various conditions to ensure its reliability and responsiveness. By leveraging existing technology, this system offers a practical and efficient solution to reduce the risk of motorcycle theft and improve daily user security. The results contribute significantly to efforts to enhance vehicle security in society.